The discursive construction of responsibility : strategies used by political and military witnesses in public hearings - Gallina, Natalia (2013)
From the perspective of current situated discourse analysis and the associated disciplinary strands of conversational analysis, narrative studies and critical discourse analysis, this study examines how political and military elite witnesses construct versions of reality in the context of the public hearing and argues for the contestable nature of such versions. This study draws upon a multimodal approach which views discourse as an inherently complex process and product involving various semiotic layers, particularly, language and gesture which are intricately interwoven. The examination of the data reveals the systematic and strategic concurrence of resources of various kinds. It is shown how carefully elaborated texts are constituted through the use of evasion strategies (refusal to answer, reformulation and impersonalization), sensemaking practices and argumentative moves (scrip-formulation, counterfactual account, recourse to the lesson-deriving frame), and choreographed non-verbal resources (bodily orientation, facial expression and gesture); and how through these resources participants manage to deflect damaging attributions of personal and institutional responsibility and blame. An exploration of conversational dynamics shows that elite witnesses are often allowed to disregard the responsibilities and obligations defined by their situational roles as interrogators fail to gain, exert and maintain interactional control. It is possible to suggest hence that these witnesses benefit from some special licences which ultimately permit them to shape content, form and information flow. This study concludes by tapping into the dialectical link between discourse and society unveiling the particular ways in which strategic public discourse represents an instrument of social manipulation and hegemonic control which, far from generating genuine public dialogue, works to manufacture a false sense of debate as well as an equally false sense of consensus and resolution.